Meeting at the crossroads: collaboration between information technology departments and health sciences libraries...116th Annual Meeting Medical Library Association, Inc. Toronto, ON, Canada May 15-20, 2015 - King, Samuel; Cataldi-Roberts, Erica; Wentz, Erin (Journal of the Medical Library Association, 2017)
Objective: The purposes of this survey were to determine the nature and extent of collaboration between health sciences libraries and their information technology (IT) departments, to identify strengths and issues connected to this relationship, and to provide examples demonstrating exceptional collaborative success. Methods: A fourteen-question survey was sent to a broad selection of health care and academic libraries through a variety of email discussion lists and was limited to one response per institution. Convenience sampling was used to collect the responses. Results: An overwhelming majority of libraries described the relationship with their IT departments as good or excellent, and there were a variety of creative joint initiatives underway. Opportunities exist for continued and expanded library/IT collaboration. Conclusions: Good quality relationships between libraries and their IT departments are essential due to the interconnected nature of their services, and fortunately, this appears to be the norm at a variety of institutions. Mutual respect, open communication, realization of each department's mission, and responsiveness to each other's needs are part of what makes these relationships successful, which in turn leads to successful collaborative ventures that bode well for the future of both services.